2015
DOI: 10.1074/jbc.m115.693150
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90·Cdc37 Complexes with Protein Kinases Form Cooperatively with Multiple Distinct Interaction Sites

Abstract: Protein kinases are the most prominent group of heat shock protein 90 (Hsp90) clients and are recruited to the molecular chaperone by the kinase-specific cochaperone cell division cycle 37 (Cdc37). The interaction between Hsp90 and nematode Cdc37 is mediated by binding of the Hsp90 middle domain to an N-terminal region of Caenorhabditis elegans Cdc37 (CeCdc37). Here we map the binding site by NMR spectroscopy and define amino acids relevant for the interaction between CeCdc37 and the middle domain of Hsp90. Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 49 publications
(67 reference statements)
9
41
0
Order By: Relevance
“…Previous results suggest that association of PP5 with Hsp90 chaperone complexes is accompanied by structural changes, because within a purified Hsp90-Cdc37-Cdk4 complex, the phospho-Ser13 Cdc37 substrate is inaccessible to dephosphorylation by the nonspecific λ-phosphatase but readily accessible to dephosphorylation by PP5 (8). This conclusion is further supported by recent results indicating that residues in the vicinity of the Ser13 are responsible for binding client kinases (9,22,23) where it is likely to be buried. A conformational change would, therefore, be required to allow PP5 access to its substrate.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Previous results suggest that association of PP5 with Hsp90 chaperone complexes is accompanied by structural changes, because within a purified Hsp90-Cdc37-Cdk4 complex, the phospho-Ser13 Cdc37 substrate is inaccessible to dephosphorylation by the nonspecific λ-phosphatase but readily accessible to dephosphorylation by PP5 (8). This conclusion is further supported by recent results indicating that residues in the vicinity of the Ser13 are responsible for binding client kinases (9,22,23) where it is likely to be buried. A conformational change would, therefore, be required to allow PP5 access to its substrate.…”
Section: Discussionsupporting
confidence: 78%
“…Phospho-Ser13 Cdc37 has a more stable and compact conformation than the WT (29), in which the phosphoSer13 is accessible to dephosphorylation by both calf intestine alkaline phosphatase (29) and λ-phosphatase (8). However, at least for the kinase B-Raf, this conformation is not a requirement for either client vs. nonclient recognition (9) or subsequent association with Hsp90 as a stable complex between Hsp90, Cdc37, and B-Raf can be formed from the individual proteins in vitro in the absence of phosphorylation (22,23), although phospho-Ser13 enhances its stability (22). These observations are consistent with recent data indicating that the primary interaction of Cdc37 with B-Raf is through a distinct C-terminal domain of Cdc37 and remote from this site of phosphorylation (9,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also a network of ionic interactions between Cdc37NTD and Hsp90MD, which explains previously identified salt sensitivity of Cdc37/Hsp90 binding (Fig 5B, bottom insert). Our structure thus helps explain recent data that C. elegans Cdc37 interacts with the middle domain of Hsp90(27), rather than the NTD as observed in previous human domain binding studies. Instead of assuming that C. elegans is different or that the interactions observed with isolated domains were incorrect, we propose that Cdc37/kinase first binds Hsp90 in its open conformation as seen in the crystal structure, and then rearranges to the site on the middle domain upon Hsp90 closure, as seen in our structure.…”
Section: Cdc37 Precisely Mimics a Conserved Feature Of Kinase N-lobe-supporting
confidence: 80%
“…Cdc37 had been shown to interact with Hsp90 during the processing of its client kinases (46,47). Our results clearly showed that disruption of the Hsp90-Cdc37 interaction by celastrol treatment during hypertrophy abrogated subsequent interactions between Hsp90 and IKK␤ in myocytes, indicating that the Hsp90-Cdc37 interaction is essential to stabilize IKK␤ prior to the formation of a ternary complex with Hsp90.…”
Section: Fig 11mentioning
confidence: 54%